Virtual help to the learning of Geology in the Madrid School of Mines and Energy - José EUGENIO ORTIZ; Trinidad DE TORRES (Ediciones Universidad de Salamanca, 2014)
Learning Geology requires a skill that is primarily achieved with practice in nature, being more effective when one tries to transmit knowledge to others. Here, we show the results of an educational innovation program in courses related to Geology using new technologies (ITC) in order to increase the acquisition of geological knowledge. This program is designed mainly on the basis of individual work with video recordings in the field in which students explain geological concepts at various scales. These videos have been uploaded to the "moodle", "facebook" and "youtube" channel, where people can view them. We also elaborated "Geological routes," which are accompanied by these videos indicating the most important geological aspects that can be observed, that were uploaded to "moodle" platform. The realization of these videos has been warmly welcomed by students, and they show increased motivation, accompanied by an improvement in grades. They also gained confidence in public speaking using technical language. Also, students can make itineraries of geological interest without having to be accompanied by a professor, deeping into the most interesting topics.